2018
DOI: 10.3390/ijms19124068
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering Therapies Based on Folic Acid and Other Vitamin B Derivatives. Functional Mechanisms and Current Applications in Regenerative Medicine

Abstract: B-vitamins are a group of soluble vitamins which are cofactors of some of the enzymes involved in the metabolic pathways of carbohydrates, fats and proteins. These compounds participate in a number of functions as cardiovascular, brain or nervous systems. Folic acid is described as an accessible and multifunctional niche component that can be used safely, even combined with other compounds, which gives it high versatility. Also, due to its non-toxicity and great stability, folic acid has attracted much attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…Significant differences in proteins and other components found between DVI‐HPL and I‐HPL, on one side, and HPL, on the other, can be attributed to the suspension of our start Intercept‐treated PC in 65% SSP+ instead of 100% plasma. The use of SSP+, to partially substitute for plasma, deprives the HPL of potentially important components, such as plasma‐borne IGF‐1, albumin, transferrin, glucose, folate, and vitamin B12, a depletion that may affect the growth of some cells . The use of SSP+ also had an impact on the chemical composition, in particular, a significant increase in phosphorus content in I‐HPL and DVI‐HPL compared to HPL.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in proteins and other components found between DVI‐HPL and I‐HPL, on one side, and HPL, on the other, can be attributed to the suspension of our start Intercept‐treated PC in 65% SSP+ instead of 100% plasma. The use of SSP+, to partially substitute for plasma, deprives the HPL of potentially important components, such as plasma‐borne IGF‐1, albumin, transferrin, glucose, folate, and vitamin B12, a depletion that may affect the growth of some cells . The use of SSP+ also had an impact on the chemical composition, in particular, a significant increase in phosphorus content in I‐HPL and DVI‐HPL compared to HPL.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, new investigations substituting ranelic acid for vitamin-B derivatives of Sr or Zn are being recently described with very promising characteristics. 117 Biocompatibility is crucial in terms of regenerative therapies; most of the studies were carried out using Zn and/or Sr doped scaffolds (bioactive glasses, nanofibers. .…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…It has been shown that these derivatives promote regenerative processes in a wide range of tissues and organs; further folic acid derivatives show a long lifespan under physiological conditions. This is the greatest limitation in regenerative therapies; e.g., when using growth factors or other recombinant proteins [90].…”
Section: Role Of Folic Acid and Vitamins B6 And B12 In Bone Regenementioning
confidence: 99%
“…Certainly, FO (the anionic form of folic acid) is a promising alternative as a Sr carrier in composites [18]. Additionally, the incorporation of B vitamins (folates) may contribute improving the metabolism and other processes in cells involved in bone regeneration [90].…”
Section: Synthesis and Properties Of Srfomentioning
confidence: 99%